2022
DOI: 10.3390/antiox11071326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2-Year Nutritional and Lifestyle Intervention on Oxidative and Inflammatory Statuses in Individuals of 55 Years of Age and over at High Cardiovascular Risk

Abstract: Obesity and overweight are disorders with high impact on the morbidity and mortality of chronic diseases, such as type 2 diabetes mellitus (T2DM) and cardiovascular diseases (CVD). We aim to assess the effects of 2-year nutritional and lifestyle intervention on oxidative and inflammatory status in individuals of 55 years of age and over at high CVD risk. Participants (n = 100 individuals of 55 years of age and over living in the Balearic Islands, Spain) were randomized into control and intervention group. Anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…The current patients with better adherence to the MedDiet showed higher levels of antioxidant enzymatic activity in their plasma, as well as better proinflammatory status than those ones with lower adherence to the MedDiet. These results are in accordance with a previous study evidencing high levels of enzymatic activity of catalase and SOD in plasma from patients with high cardiovascular risk after an intervention with the MedDiet [ 65 ]. Moreover, it was observed that after 6 months of lifestyle intervention, IL-6 and TNFα were decreased, although only significantly for IL-6 in the group with high adherence to the MedDiet [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…The current patients with better adherence to the MedDiet showed higher levels of antioxidant enzymatic activity in their plasma, as well as better proinflammatory status than those ones with lower adherence to the MedDiet. These results are in accordance with a previous study evidencing high levels of enzymatic activity of catalase and SOD in plasma from patients with high cardiovascular risk after an intervention with the MedDiet [ 65 ]. Moreover, it was observed that after 6 months of lifestyle intervention, IL-6 and TNFα were decreased, although only significantly for IL-6 in the group with high adherence to the MedDiet [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…In another study, levels of total antioxidant capacity, reduced glutathione, MDA, and CRP were reduced 4 months after RYGB surgery [12]. Regarding LS trials, Monserrat-Mesquida [16] reported that a two-year nutritional and lifestyle intervention could reduce oxidative and inflammatory status, resulting in a reduction in CVD risk in individuals with high CVD risk. On the other hand, LS interventions did not produce any amelioration in the OS in women with obesity and infertility with modest weight loss [15].…”
Section: Discussionmentioning
confidence: 99%
“…Amelioration of oxidative stress in form of a reduction in plasma levels of monocyte chemoattractant protein-1 (MCP1), xanthine oxidase, malondialdehyde (MDA), and myeloperoxidase is an additional benefit of long-term lifestyle intervention [15]. This indicates that oxidative stress has strong associations with biomarkers of cardiometabolic health [16]. The literature has few studies prospectively comparing BS versus lifestyle intervention regarding effects on oxidative, inflammatory, and cardiovascular disease risk in patients with obesity, especially in the Arabic region.…”
Section: Introductionmentioning
confidence: 99%
“…In neutrophils and PBMCs, ROS production was determined after being activated with zymosan A (ZYM) (1 mg/mL PBS) from Saccharomyces cerevisiae (Sigma-Aldrich) and lipopolysaccharide (LPS) (100 µg/mL phosphate-buffered saline (PBS)), following the previously described protocol [31].…”
Section: Ros Production In Neutrophils and Pbmcsmentioning
confidence: 99%